Evaluasi Strategi Pengelolaan untuk Menyikapi Peluang dan Tantangan dalam Menghadapi Era Modern yang Terus Berkembang - Azzahra Meytriana; Dewi Jannati Asih Putri; Mustika Wulandari; Siti Zulaikha (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Zakat is a key pillar of the Islamic economic and social system, serving not only as an obligatory act of worship but also as a vital instrument for economic equality and improving the welfare of the people. In Indonesia, zakat management is regulated by various laws and regulations, with official institutions such as the National Zakat Agency (BAZNAS) and the Zakat Collection Institutions (LAZ) responsible for collecting and distributing zakat. The rapidly developing digital era has opened up significant opportunities for improving zakat management, particularly in terms of efficiency, transparency, and ease of access through online platforms. Utilizing this technology can facilitate the community in fulfilling their zakat obligations and expedite the distribution process to those entitled to it. However, although the national zakat potential is estimated to reach trillions of rupiah, the realization of zakat collection remains far from the expected figure. This gap indicates major challenges in several aspects, such as low zakat literacy in the community, a lack of transparency in zakat management, and issues related to efficiency and accountability in the management of zakat funds. Therefore, this study aims to delve deeper into the existing obstacles and opportunities that can be exploited in zakat management in the digital era. Using a qualitative research approach with a literature review method, this study seeks to identify factors influencing zakat management, including regulatory, institutional, and public perception aspects. This study also formulates innovative and adaptive strategies that can be implemented to optimize zakat management. It is hoped that the results of this study will contribute to creating a more effective, efficient, and transparent zakat management system, thereby playing a greater role in supporting the economic development of the community.